BONE SEVERE FORM OF HYPERPARATHYROIDISM IN A PATIENT WITH ADENOMA OF PARATHYROID GLAND - K. M. Petrosyan; N. V. Severskaya; D. N. Derbugov; A. A. Kuril'chik; N. V. Zhelonkina; A. V. Dement'ev; E. I. Kupriyanova; G. A. Davydov; A. D. Kaprin; V. N. Galkin; S. A. Ivanov (Исследования и практика в медицине)
Hyperparathyroidism is one of the most common endocrinopathies. This disease leads to a violation of phosphorus-calcium metabolism and the washing out of calcium from bone tissue. Breach of the skeleton’s structure in hyperparathyroidism is often mistaken for metastatic bone damage, which leads to incorrect treatment tactics. In this work we present the clinical observation of a patient with an adenoma of the parathyroid gland and a severe bone form of hyperparathyroidism. Multiple lesions of bones with destruction of the cortical layer and the presence of the softtissue component were initially regarded as metastases in the bone. However, the morphological pattern of bone foci, as well as an elevated level of calcium and parathyroid hormone, made it possible to diagnose the bony form of hyperparathyroidism. The search for the cause of hyperparathyroidism revealed a tumor in the projection of the right lower parathyroid gland. Surgical removal of parathyroid adenoma led to the normalization of the level of calcium and parathyroid hormone. The article presents data of laboratory-instrumental methods of research and the results of surgical treatment of a patient.